MORPHOMETRIC DIFFERENCES OF KINTAMANI BALI DOG MALE AND BITCH IN THE DEVELOPMENT PHASE - Ruslie, Sabella Ivana; Suartini, I Gusti Ayu Agung; Sampurna, I Putu (Buletin Veteriner Udayana, 2022)
Kintamani dogs are native dogs of Indonesia which have been registered with the Fédération Cynologique Internationale (FCI) as medium-sized dogs. This study aims to determine the morphometric differences of male and female Kintamani Bali Dog (AKB) in the development phase that is maintained in Bangli Regency and Denpasar Municipality. A total of 32 Kintamani Bali Dogs (AKB), consisting of 8 male AKB from Bangli, 8 female AKB from Bangli, 8 male AKB from Denpasar, and 8 female AKB from Denpasar, were used in this study to determine the forefoot and hind limb morphometry in developmental phase (6-18 months). The variables measured were hind limb height (TB), upper hind limb length (HF), lower hind limb length (TP), hind limb length (QH), hind limb height (HR), upper hind limb length (RC), lower front foot length (FF), front toe length (QF). The data obtained were analyzed by variant analysis using SPSS version 25. The results showed that the HR, RC, QF and HF were significantly different (P<0.05) between male AKB maintained in Bangli Regency and Denpasar Municipality; while the height of the TB was significantly different (P>0.05) between female AKB maintained in Bangli Regency and the Municipality of Denpasar. This study shows that the feed and the way of maintenance is very influential on the growth of male and female AKB with different topography, cage modification can be done to equalize the conditions in the place of origin so as to minimize temperature differences that can result in differences in metabolic functions that affect the growth rate.